Metal(II)–Organic Coordination Polymers Modulated by Two Isomeric Semirigid Bis‐Pyridyl–Bis‐Amide Ligands: Structures, Fluorescent Sensing Behavior, and Selective Photocatalysis. Issue 12 (1st September 2014) - Wang, Xiu‐Li; Luan, Jian; Lin, Hong‐Yan; Lu, Qi‐Lin; Le, Mao; Liu, Guo‐Cheng; Shao, Ji‐Yan
Abstract A series of metal–organic coordination polymers based on two isomeric semirigid bis‐pyridyl–bis‐amide ligands and 5‐methylisophthalic acid (5‐H2MIP), namely, [Cu(3‐bpah)(5‐MIP)]⋅2 H2O (1), [Ni(3‐bpah)(5‐MIP)]⋅H2O (2), [Co(3‐bpah)(5‐MIP)]⋅H2O (3), [Cu(4‐bpah)(5‐MIP)(H2O)] (4), [Ni(4‐bpah)(5‐MIP)(H2O)]⋅H2O (5), [Co(4‐bpah)(5‐MIP)] (6), [Zn(4‐bpah)(5‐MIP)] (7), and [Cd(4‐bpah)(5‐MIP)] (8) (3‐bpah=N, N′‐bis(3‐pyridinecarboxamide)‐1, 2‐cyclohexane, 4‐bpah=N, N′‐bis(4‐pyridinecarboxamide)‐1, 2‐cyclohexane), have been hydrothermally synthesized and structurally characterized by elemental analysis, IR spectroscopy, powder X‐ray diffraction, thermogravimetric analysis, and single‐crystal X‐ray diffraction analyses. The title coordination polymers display versatile structural features with one‐, two‐, and three‐dimensional frameworks. Complex 1 exhibits a two‐dimensional (4, 4) network named as type c, which is constructed from the arched 3‐bpah and 5‐MIP anions with alternating orientations. Complexes 2 and 3 show similar three‐dimensional frameworks, which feature a trinodal (2, 3, 5)‐connected topology with the Schläfli symbol of (42⋅6⋅84⋅102⋅12)(42⋅6)(8). Complex 4 exhibits an undulated two‐dimensional (4, 4) network of type b, in which the twist angles of the ligands are different from those of 1. Complex 5 reveals a one‐dimensional double‐strand chain, whereas complexes 6–8 exhibit similar two‐dimensional double‐layer structures with (42⋅6)(43⋅6⋅84⋅102)(4) topology. The influence of semirigid bis‐pyridyl–bis‐amide ligands and central metals on the structures of the title complexes has been reported. The fluorescent sensing behaviors of complexes 7 and 8, and the electrochemical and photocatalytic properties of complexes 1–6 have also been investigated in detail.